Penerapan ISO 16140-3:2021 untuk Pencacahan Enterobacteriaceae pada Produk Pangan - Nagur, Kemala S.; Surati, Sri; Marusaha Sitorus , Aditya Anugerah; Cahyaningsih, Eni; Putri, Fannisa; Wilasti, Yulin (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
Method verification is one of the steps required to ensure that all methods used meet the standards required for data reliability and accuracy in a laboratory that implements Good Laboratory Practices (GLP). In accordance with ISO 16140-3:2021, the method verification for microbiology testing implemented by calculating the Intralaboratory Reproducibility Standard Deviation (SIR) for implementation verification and eBias value for food item verification. Method verification for enumeration of Enterobacteriaceae in food products using ISO 16140-3 has never been carried out at the Indonesian Food and Drug Authority (FDA) laboratories. Therefore, verification of this method needs to be performed. This study aimed to verify the ISO 21528-2:2017 as reference method for enumeration of Enterobacteriaceae in food products by colony count technique. The selected food item for implementation verification was pasteurized milk while for food item verification, the selected food items were yogurt, traditional preserved egg (telur pindang), sweet and hard candy, seasoning dry powder, worcester sauce and cassava chips. All of selected foods were artificially contaminated with Escherichia coli WDCM 00012. The SIR value obtained was 0.12 ≤ 2× 0,18 (lowest mean value of SR from ISO 21528-2:2017), indicating that the acceptability limit for the implementation verification was met. While the eBias value for all selected food item were less than 0,5 log10, thus the verification study in the National Quality Contol Laboratory of Drug and Food (NQCLDF), Indonesian FDA, meets the acceptance criteria defined in the standard ISO 16140-3:2021.